Pengaruh budaya modern terhadap agama: konteks agama - Nurselly, Tania Tiara (Maliki Interdisciplinary Journal, 2025)
Indonesia is a large country that has a variety of cultures. Cultural diversity in Indonesia is influenced by many factors, one of which is influenced by religion. Religion has a big role in the development of culture in Indonesia, and vice versa. Culture has a role in the development of a religion. This paper is intended to show that religion and culture have a very close relationship. The two have a connection that is difficult to separate. The researcher uses the literature study method in this study, so the researcher uses a qualitative method, namely by using descriptive data. The end result of this study is that people who do not realize that religion and culture are related will know that it cannot be separated. And also in culture there are religious values, as well as in religion there are cultural values.